Biosynthesis of the Stress-Protectant and Chemical Chaperon Ectoine: Biochemistry of the Transaminase EctB - Richter, Alexandra A.; Mais, Christopher-Nils; Czech, Laura; Geyer, Kyra; Hoeppner, Astrid; Smits, Sander H. J.; Erb, Tobias J.; Bange, Gert; Bremer, Erhard (Frontiers in Microbiology, 2019)
Bacteria frequently adapt to high osmolarity surroundings through the accumulation of compatible solutes. Ectoine is a prominent member of these types of stress protectants and is produced via an evolutionarily conserved biosynthetic pathway beginning with the L-2,4-diaminobutyrate (DAB) transaminase EctB. Here, we studied EctB from the thermo-tolerant Gram-positive bacterium Paenibacillus lautus and show that this tetrameric enzyme is highly tolerant to salt, pH, and temperature. During ectoine biosynthesis, EctB converts L-glutamate and L-aspartate-beta-semialdehyde into 2-oxoglutarate and L-2,4-diaminobutyrate, but it also catalyzes the reverse reaction. Our analysis unravels that EctB enzymes are mechanistically identical to the PLP-dependent gamma-aminobutyrate transaminases (GABA-TAs) and only differ with respect to substrate binding. Inspection of the genomic context of the ectB gene in P. lautus identifies an unusual arrangement of juxtapositioned genes for ectoine biosynthesis and import via an Ehu-type binding-protein-dependent ABC transporter. This operon-like structure suggests the operation of a highly coordinated system for ectoine synthesis and import to maintain physiologically adequate cellular ectoine pools under osmotic stress conditions in a resource-efficient manner. Taken together, our study provides an in-depth mechanistic and physiological description of EctB, the first enzyme of the of the ectoine biosynthetic pathway.